National Dissemination of Chronic Disease Self-Management Education Programs: An Incremental Examination of Delivery Characteristics - Smith, Matthew Lee; Ory, Marcia G.; Ahn, SangNam; Kulinski, Kristie P.; Jiang, Luohua; Horel, Scott; Lorig, Kate (Frontiers in Public Health, 2015)
*